Fabrication of PVA/graphene nanofibrous membrane infused with neem extraction for packaging and biomedical applications - Syed Rashedul Haque; Mohammad Asaduzzaman Chowdhury; Md. Masud Rana; Nayem Hossain (SN Applied Sciences, 2023)
Abstract Graphene nanofibrous membranes have been synthesized in the present study by combining neem with graphene and using polyvinyl alcohol (PVA). The nanofibrous membranes have been synthesized using an electrospinning under optimum processing conditions for food packaging and biomedical applications. The FTIR analysis confirmed the presence of different organic compounds in the materials. XRD analysis confirmed the crystallinity of the fabricated materials. The minimum average diameter of the fibers was 276.9 nm, approved by the SEM images. The fabricated materials contained Al as the maximum atomic percentage confirmed by the EDX analysis. All the samples had the same top absorption rate. The addition of neem increased the thermal stability of the materials, approved by the thermal analysis. The maximum bacterial reduction rate was observed against the gram-negative bacteria strain Escherichia coli in sample R3. The results demonstrated that the synthesized nanofibrous membranes can be used for biomedical applications.